A COMPARATIVE STUDY BETWEEN CLOMIPHENE CITRATE WITH TIMED INTERCOURSE VS CLOMIPHENE CITRATE WITH IUI - MADHU UDAWATH M.S., D.G.O. (International Journal of Pharma and Bio Sciences, 2014)
Infertility is a condition caused due to both female and male factors and IUI can be the solution to many of these factors especially in unexplained infertility. A study involving 200 couples with nil female factors and normal semen parameters with an average period of 2-8 years of primary infertility were taken into consideration. The dose of clomiphene citrate was administered at 100mg/day from D2-D6 and follicles were monitored from D7 until the day of rupture, hcG 5000IU was given when the dominant follicle reached an average size of 18-20mm for both the study groups. This study aims to compare the success rates of ovulation induction and timed intercourse Vs intra-uterine insemination.